2002
DOI: 10.1016/s0893-133x(02)00295-6
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar Vulnerability to Nicotine Oral Self-administration in Mice during Early Adolescence

Abstract: (10 mg/l). After a 6-day period, a fading study was carried out, in which nicotine concentration was reduced to 7 mg/l (days 7-9) and 5 mg/l (days 10-12), to assess whether animals would compensate by increasing their intake from the nicotine solution. In Experiment 2, psychopharmacological effects on locomotion induced by the nicotine solution (0, 10, 30 mg/l) Recent research has emphasized that adolescence is associated with patterns of temporary deviance (Arnett 1992) and the use of various kinds of ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
142
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(170 citation statements)
references
References 73 publications
(111 reference statements)
21
142
2
1
Order By: Relevance
“…Adolescents smoke significantly fewer cigarettes than adults, yet experience higher rates of dependence at the same levels of use (Kandel and Chen, 2000). In line with the human findings, much of the data gathered from animals also reflect a peculiar vulnerability to nicotine in adolescence (Laviola et al, 1999;Adriani et al, 2002). In mice, it seems that early adolescence in particular (during the period just preceding puberty) is the developmental phase responsible for the pattern of behaviors constituting sensitivity to nicotine's effects (Adriani et al, 2002).…”
Section: Introductionmentioning
confidence: 62%
“…Adolescents smoke significantly fewer cigarettes than adults, yet experience higher rates of dependence at the same levels of use (Kandel and Chen, 2000). In line with the human findings, much of the data gathered from animals also reflect a peculiar vulnerability to nicotine in adolescence (Laviola et al, 1999;Adriani et al, 2002). In mice, it seems that early adolescence in particular (during the period just preceding puberty) is the developmental phase responsible for the pattern of behaviors constituting sensitivity to nicotine's effects (Adriani et al, 2002).…”
Section: Introductionmentioning
confidence: 62%
“…C57BL/6 mice were chosen because prior reports demonstrate that adult and periadolescent mice from this strain consume nicotine in the concentration used in the present study. In fact, oral nicotine has also been shown to be effective in eliciting behavioral (Adriani et al, 2002(Adriani et al, , 2004Gaddnas et al, 2001) and neurochemical alterations, including nicotinic receptors upregulation (Nuutinen et al, 2005;Sparks and Pauly, 1999), altered monoamine levels, and metabolism (Gaddnas et al, 2000;Tammimaki et al, 2006;Vihavainen et al, 2006) as well as altered expression of genes implicated in synaptic plasticity induced by drugs of abuse (Marttila et al, 2006) and in Alzheimer's disease (Gutala et al, 2006) in this and other mouse strains. This strain of mice is known to present particular features, such as higher voluntary ethanol consumption (Crawley et al, 1997), which should be taken into consideration in studies that involve the administration of this substance, even though the bases underlying these strain-specific characteristics remain poorly understood (Crabbe et al, 1999).…”
Section: Methodological Issuesmentioning
confidence: 90%
“…We have used a brief exposure period and a low dose of nicotine, given by intravenous injection, in order to better model early teenage smoking than the modes of chronic administration used in previous studies [1,3,19]. Intravenous administration of nicotine is less stressful than subcutaneous or intraperitoneal injections, gives equivalent amounts of drug as the animal matures, and more closely mimics the pharmacokinetics of smoking.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…When given a two bottle choice, early adolescent mice [postnatal day (P) were the only group to prefer nicotine solution over water [3]. In conditioned place preference (CPP) studies, periadolescent rats were shown to exhibit a highly significant preference for the nicotine-paired compartment whereas adult rats did not [6,47].…”
Section: Introductionmentioning
confidence: 99%